1987
DOI: 10.1128/jcm.25.4.685-691.1987
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter hyointestinalis associated with human gastrointestinal disease in the United States

Abstract: Campylobacter hyointestinalis was isolated from stool specimens of four persons, all of whom were experiencing nonbloody, watery diarrhea. The youngest (8 months of age) and the oldest (79 years of age) individuals were females, and the other two were homosexual men. C. hyointestinalis was the only clinically significant pathogen isolated from stool specimens for three of the individuals. In case 3 (involving a 37-year-old homosexual man), Entamoeba histolytica and Shigella sonnei were also present in the stoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…Although C. hyointestinalis has been implicated to be aetiological agent of enteric disease in pig, human and mollucan rusa deer ( GEBHART et al, 1983;EDMONDS et al, 1987;HILL et al, 1987), there is no study directly reporting this organism as a cause of bovine diarrhea. URSING et al (1984) and OHYA et al (1988) used a few C. hyointestinalis strains isolated from bovine chronic diarrhea in their studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although C. hyointestinalis has been implicated to be aetiological agent of enteric disease in pig, human and mollucan rusa deer ( GEBHART et al, 1983;EDMONDS et al, 1987;HILL et al, 1987), there is no study directly reporting this organism as a cause of bovine diarrhea. URSING et al (1984) and OHYA et al (1988) used a few C. hyointestinalis strains isolated from bovine chronic diarrhea in their studies.…”
Section: Resultsmentioning
confidence: 99%
“…Campylobacter hyointestinalis was recently proposed as a new species to accommodate Campylobacter strains isolated from pigs with lesions of proliferative ileitis ( GEBHART et al, 1983;GEBHART et a]., 1985). Since the first report of C. hyointestinalis isolated from pigs, phenotypically similar bacteria have been isolated from cattle feces and stool specimens of human (FIREHAMMER and BORDER, 1986; SNODGRASS et al, 1986;EDMONDS et al, 1987). O n the basis of phenotypic and DNA-related data it has been confirmed that pig, cattle and human isolates are the same species ( GEBHART et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…sputorum and Camp. upsaliensis, are increasingly being implicated in human disease (Fennel et al 1986;Edmonds et al 1987;Goossens et al 1990;Lindblom et al 1995). In England and Wales, confirmed cases of campylobacter diarrhoea have exceeded those due to salmonella since 1981, with about 44 000 reported cases in 1995 compared with 30 000 due to salmonella (ACMSF 1993;Anon.…”
Section: Introductionmentioning
confidence: 99%
“…is exceedingly difficult, the real prevalence might be higher. Hitherto Campylobacter hyointestinalis has been associated only sporadically with human gastrointestinal disorders (Edmonds et al, 1987;Gorkiewicz et al, 2002). Even though the prevalence for Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%